Overview Of Bullying Behavior Among Nursing Students In Gorontalo Province - Soeli, Yuniar Mansye; Firmawaty, Firmawaty; Wulansari, Ika; Antu, Mihrawaty S; Rahim, Nirwanto K (Jambura Nursing Journal, 2024)
One of the sources of problems in the educational environment is the presence of mild aggressive behavior among teenagers, such as teasing, hitting, pushing, or threatening each other. This behavior is known as bullying. There have been many cases of bullying in Gorontalo, as reported by various media, including Gorontalo Daily News. The purpose of this research is to describe the bullying behavior among nursing students in Gorontalo Province. The type of research used is descriptive research with a retrospective approach, examining the bullying behavior of nursing students in Gorontalo Province. The population in this study consisted of 1,403 students, while the sample size was 311 respondents. The results showed that the depiction of bullying behavior among nursing students in Gorontalo Province included 300 respondents in the low category, 142 respondents in the moderate category, and 1 respondent in the high category. Thus, the bullying behavior among nursing students in Gorontalo Province is classified as low. Therefore, it can be concluded that the bullying behavior among nursing students in Gorontalo Province is considered low.